Establishment and application of a new diagnostic definition of metabolic syndrome in the Shantou region of southern China - Ding, Zan (Sci Rep, 2016)
The existing definitions of metabolic syndrome (MetS) may not be fully appropriate for the Shantou population because of ethnic and regional differences. We sought to establish a 95% multivariate medical reference range (MMRR) model for diagnosing MetS in Shantou adults and to evaluate the prevalence of MetS by the MMRR, JCDCG (the Chinese Guidelines), and International Diabetes Federation (IDF) criteria. A total of 4,580 participants were recruited in Shantou, southern China. We developed a MMRR model based on the combinatorial indicatrixes method for three categorized indicatrixes. According to the developed MMRR criteria, men (women) in Shantou have MetS by meeting 3 or more of the following: waist circumference ≥89 (81) cm; triglycerides level ≥1.73 (1.64) mmol/L; high-density lipoprotein cholesterol level ≤1.07 (1.05) mmol/L; blood pressure ≥138/89 (136/85) mmHg; and fasting plasma glucose ≥5.8 (5.7) mmol/L. The agreement of the MMRR with JCDCG and IDF criteria was “substantial” (both κ > 0.68), but the recommended reference values and proportion of individual components of MetS defined by the 3 criteria differed. The population-based MMRR criteria may be appropriate for diagnosing MetS in Shantou population and the model might be useful for generalization to other geographic regions.